A functional trait‐based approach to assess the impact of an alien palm invasion on plant and soil communities on a South Pacific island. (12th January 2021) - Forey, Estelle; Lodhar, Sherri; Gopaul, Sunil; Boehmer, Hans Juergen; Chauvat, Matthieu
Abstract: In island ecosystems, biological invasions are one of the major threats to native biodiversity and to ecosystem functioning. Invasive ornamental plants such as the alien palm tree Pinanga coronata in the Fiji islands can form mono‐dominant stands in rainforests and displace native species. Using a functional trait‐based approach, we investigated the impact of P. coronata on both above and belowground communities (i.e. plants and Collembola). Within a rainforest reserve on Fiji´s principal island, we sampled a total of 10 invaded and non‐invaded plots and recorded five functional traits for plants and six for Collembola. We found that invasion by P. coronata led to a strong and significant decrease of native plants and Collembola taxonomic diversity. Ingress of P. coronata also induced a decrease in the functional diversity of plant communities and to a lesser extent of Collembola communities. P. coronata invasion led to a decrease of leaf carbon–nitrogen ratio (LCN), Leaf nitrogen content (LN), specific leaf area (SLA) and leaf dry matter content (LDMC) of plant communities, suggesting a change in litter properties compared to non‐invaded communities. Plots with P. coronata were associated with large Collembola living at the soil surface with more trichobothria and pseudocelli, which are used as defence mechanisms. Using trait‐matching, we also found that the strength of plant‐soil relationships was higher (i.e. more stable) in non‐invaded plots than in P. coronata ‐invaded plots. Lastly this study suggests that the main mechanism through which P. coronata alters soil communities is a change in plant properties rather than a change in the abiotic environment. Our trait‐based approach underlines the negative impact of this alien palm invasion on native rainforest plant and soil fauna in Fiji, and the urgent need for on‐the‐ground action to conserve terrestrial island biodiversity in Fiji´s rainforests.